Campaña electoral Ecuador 2021: análisis comparativo de las estrategias de comunicación política de los candidatos a la presidencia Guillermo Lasso y Andrés Arauz en Twitter (Monográfico) - Mina Mendoza, Arnaldo Javier (2023)
In the wake of the global pandemic, electoral campaigns have turned much more to the digital world and have become the focus of media and social media attention. In this context, the candidates for the 2021 presidential elections in Ecuador have proposed to turn the traditional and monotonous electoral contests through the digital world. The objective of this research is to analyze and rank the different political communication strategies on Twitter of the presidential candidates that had the greatest influence and prominence in the first electoral campaign within the period between December 31 and February 4. For the study, the candidates of the two main political parties were selected: on the one hand, the leader of the opposition, Guillermo Lasso. On the other, the heir to the legacy of Correismo, Andrés Arauz. From a content analysis methodology with a quantitative, qualitative, and discursive approach, what was done was to study the political communication strategies on Twitter. It was based mainly on a study of the social network of the candidates, their level of interaction and time of the publications. Finally, the central axes of the tweets issued, and the discursive line of their publications were identified to investigate their possible target audience and what they were trying to communicate to active users on social networks.